PEMILIHAN GURU TERINOVATIF DI MASA PANDEMI COVID-19 MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) DAN FUZZY MULTIPLE ATTRIBUTE DECISION MAKING (FMADM) DI SEKOLAH DASAR - Johnny Anwar Angkasa; Alyauma Hajjah (JTIK (Jurnal Teknik Informatika Kaputama), 2022)
Metta Maitreya Elementary School runs an innovative teacher selection program during the COVID-19 pandemic to increase teacher’s work spirit and motivation. To obtain a sportive and effective election result, the authors use the Simple Additive Weighting (SAW) and Fuzzy Multiple Attribute Decision Making (FMADM) methods. The FMADM method is used to assign the weight value to each criteria and to process the data into fuzzy numbers to process it into a crisp number while the SAW method is used to obtain ranking results based on the weight value of the predetermined criteria. Several criteria and sub-criteria are used to support the assessment in the selection. The programming language used is PHP and the database is MySQL to design and build applications. The results of the selection are presented in the form of a ranking of a number of alternatives. The results of calculations in the program can provide the same calculation results as the results of manual calculations, namely Maitrisia as the best alternative with a value of 3,5. With this program for selecting the most innovative teachers during the COVID-19 pandemic at Metta Maitreya Elementary School, it’s hoped that it will make the leader feel easier to select the most innovative teachers.